Analyzing Dynamical Behavior of Tuberculosis Transmission (Contemporary Mathematics, 2023)
In this article, we investigated the dynamical behavior of a fuzzy mathematical model with tuberculosis (TB) treatment function. The considered model analyzes fuzzy basic reproduction numbers and stability analysis for both local and global stability conditions around disease-free equilibrium points, as well as its local stability conditions around endemic equilibrium points. We examine the TB model’s sensitivity analysis with a focus on the variation of each of its parameters. We propose predicting the extension of the virus load in TB using fuzzy bifurcation. At the end, we have given a numerical simulation to illustrate the outcomes by considering some special types of treatment functions.
Keywords: tuberculosis (TB) infection model; stability analysis; bifurcation; fuzzy basic reproduction number; control system; homotopy perturbation method